Rapid conversion of replicating and integrating Saccharomyces cerevisiae plasmid vectors via Cre recombinase. Issue 12 (2nd October 2021) - Nickerson, Daniel P; Quinn, Monique A; Milnes, Joshua M
Abstract: Plasmid shuttle vectors capable of replication in both Saccharomyces cerevisiae and Escherichia coli and optimized for controlled modification in vitro and in vivo are a key resource supporting yeast as a premier system for genetics research and synthetic biology. We have engineered a series of yeast shuttle vectors optimized for efficient insertion, removal, and substitution of plasmid yeast replication loci, allowing generation of a complete set of integrating, low copy and high copy plasmids via predictable operations as an alternative to traditional subcloning. We demonstrate the utility of this system through modification of replication loci via Cre recombinase, both in vitro and in vivo, and restriction endonuclease treatments.